The educational philosophy of Luis Emilio Recabarren - Rueda, María Alicia, author.
1 online resource (xxiv, 135 pages)
Keywords: "Through close analysis of the textual archives and press writings, The Educational Philosophy of Luis Emilio Recabarren offers comprehensive insight into Recabarren's belief in education as essential to the empowerment, emancipation, and political independence of the working class, and emphasises the importance he placed on the education of workers through experiential learning in their organizations and press. By situating his work amongst broader political and educational movements occurring in Latin America in an era of imperialism, the text also demonstrates the progressive nature of Recabarren's work"--